Inhibition of spleen tyrosine kinase as treatment of postoperative ileus. Issue 11 (13th December 2012) - van Bree, Sjoerd H W; Gomez-Pinilla, Pedro Julian; van de Bovenkamp, Fleur Suzanne; Di Giovangiulio, Martina; Farro, Giovanna; Nemethova, Andrea; Cailotto, Cathy; de Jonge, Wouter J; Lee, Kevin; Ramirez-Molina, Cesar; Lugo, Dave; Skynner, Michael J; et al.
Abstract : Objective: Intestinal inflammation resulting from manipulation-induced mast cell activation is a crucial mechanism in the pathophysiology of postoperative ileus (POI). Recently it has been shown that spleen tyrosine kinase (Syk) is involved in mast cell degranulation. Therefore, we have evaluated the effect of the Syk-inhibitor GSK compound 143 (GSK143) as potential treatment to shorten POI. Design: In vivo: in a mouse model of POI, the effect of the Syk inhibitor (GSK143) was evaluated on gastrointestinal transit, muscular inflammation and cytokine production. In vitro: the effect of GSK143 and doxantrazole were evaluated on cultured peritoneal mast cells (PMCs) and bone marrow derived macrophages. Results: In vivo: intestinal manipulation resulted in a delay in gastrointestinal transit at t=24 h (Geometric Center (GC): 4.4±0.3). Doxantrazole and GSK143 significantly increased gastrointestinal transit (GC doxantrazole (10 mg/kg): 7.2±0.7; GSK143 (1 mg/kg): 7.6±0.6), reduced inflammation and prevented recruitment of immune cells in the intestinal muscularis. In vitro: in PMCs, substance P (0–90 μM) and trinitrophenyl (0–4 μg/ml) induced a concentration-dependent release of β-hexosaminidase. Pretreatment with doxantrazole and GSK143 (0.03–10 μM) concentration dependently blocked substance P and trinitrophenyl induced β-hexosaminidase release. In addition, GSK143 was able to reduce cytokine expression in endotoxin-treated bone marrow derived macrophages in a concentration-dependent manner. Conclusions: The Syk inhibitor GSK143 reduces macrophage activation and mast cell degranulation in vitro. In addition, it inhibits manipulation-induced intestinal muscular inflammation and restores intestinal transit in mice. These findings suggest that Syk inhibition may be a new tool to shorten POI.